Analysis of the Influence of Service Quality on Consumer Satisfaction at Anugerah Lau Dendang Store - Putri, Yuzia Eka; Akmal, Nikmat Puspita; Anugerah, Ajeng Inggit (Journal of Community Research and Service, 2023)
The background of this research is the decrease in sales volume at Anugerah Shop which has been detected for six months. This study aims to see the effect of service quality on customer satisfaction at Anugerah Shop. This research is classified in quantitative research. The research population is consumers who make purchases at Anugerah Shop. The data analysis technique used is descriptive data analysis, data analysis requirements test consisting of normality and homogeneity tests, and hypothesis testing with hypothetical testing and ANOVA testing. The results of the hypothesis test show that service quality has a significant effect on Anugerah Shop customer satisfaction. Based on the results of the analysis, it is known that t count = -.077 with sig = 0.00 <0.05. Shows that service quality has a significant effect on customer satisfaction at Anugerah Stores. The results of the F test show Fhit of 73.009 with a significant value = 0.00, so there is a significant influence between the independent variable, namely service quality and the dependent variable, namely customer satisfaction at Anugerah Lau Dendang Shop.